Hemagglutinin from the H5N1 Virus Activates Janus Kinase 3 to Dysregulate Innate Immunity - Xu, Wei; Chen, Minhui; Ge, Nanhai; Xu, Jun (PloS one, 2012)
Highly pathogenic avian influenza viruses (HPAIVs) cause severe disease in humans. There are no effective vaccines or antiviral therapies currently available to control fatal outbreaks due in part to the lack of understanding of virus-mediated immunopathology. In our study, we used hemagglutinin (HA) of H5N1 virus to investigate the related signaling pathways and their relationship to dysregulated innate immune reaction. We found the HA of H5N1 avian influenza triggered an abnormal innate immune signalling in the pulmonary epithelial cells, through an unusual process involving activation of Janus kinase 3 (JAK3) that is exclusively associated with γc chain and is essential for signaling via all γc cytokine receptors. By using a selective JAK3 inhibitor and JAK3 knockout mice, we have, for the first time, demonstrated the ability to target active JAK3 to counteract injury to the lungs and protect immunocytes from acute hypercytokinemia -induced destruction following the challenge of H5N1 HA in vitro and in vivo. On the basis of the present data, it appears that the efficacy of selective JAK3 inhibition is likely based on its ability to block multiple cytokines and protect against a superinflammatory response to pathogen-associated molecular patterns (PAMPs) attack. Our findings highlight the potential value of selective JAK3 inhibitor in treating the fatal immunopathology caused by H5N1 challenge.